2012
DOI: 10.1039/c2cc18132k
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of spontaneous resolution of ketoprofen with a racemic crystal structure by simple crystallization under nonequilibrium preferential enrichment conditions

Abstract: Nearly racemic ketoprofen, which satisfies the requirements for the occurrence of preferential enrichment, was spontaneously resolved into the two enantiomers by simple crystallization under nonequilibrium conditions using high concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…This difference can be correlated with the molecular organization in dl ‐ 2 and dl ‐ 3 ; thus, an undesired robust crystal structure without a planar 2D sheet should prevent the selective redissolution of homochiral chains during the crystallization process (3 b, c and Supporting Information Figure S1b, S1c). We emphasize that the first generation of chiral organic compounds10 and other racemic compounds14, 15 that were found to exhibit good to excellent PE all have the space group P ${\bar 1}$ . Thus, the absence of mirror/glide symmetry constraints for the redissolution of the homochiral chains may be important for PE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference can be correlated with the molecular organization in dl ‐ 2 and dl ‐ 3 ; thus, an undesired robust crystal structure without a planar 2D sheet should prevent the selective redissolution of homochiral chains during the crystallization process (3 b, c and Supporting Information Figure S1b, S1c). We emphasize that the first generation of chiral organic compounds10 and other racemic compounds14, 15 that were found to exhibit good to excellent PE all have the space group P ${\bar 1}$ . Thus, the absence of mirror/glide symmetry constraints for the redissolution of the homochiral chains may be important for PE.…”
Section: Resultsmentioning
confidence: 99%
“…PE is a unique, chiral symmetry‐breaking spontaneous enantiomeric resolution phenomenon that is caused by the polymorphic transition of an incipient metastable polymorphic form into a thermodynamically more stable form during crystallization from supersaturated solution of a certain kind of racemic mixed crystals (Figure 1 b). 10, 12 Recently, we have demonstrated that PE is applicable to several cases of racemic compound crystals, which turned out to behave like a racemic mixed crystal under non‐equilibrium crystallization conditions at high supersaturation 1315. The mechanism of PE, which was proposed on the basis of extensive studies on the first‐generation of chiral organic compounds (two‐component onium sulfonate salts) that showed PE (Figure 1 b), involves several successive key processes (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Since the discovery of the first compound showingP E, [9] more than twenty analogousf irstgeneration chiral organic compounds including 1-5 were found to exhibit the same PE phenomenon ( Figure 2). [10] Furthermore, quite recently,i th as been revealedt hat PE is applicable to two amino acids (alanine and leucine), [13] the twocomponent cocrystalo fdl-phenylalanine [14] or dl-arginine [15] with fumaric acid, the cocrystal of leucine with oxalic acid, [16] and ketoprofen, [17] which are classifieda saconventional "racemic compound" crystal composed of ar egular packing of pairs of R and S enantiomers or a" racemicm ixed crystal (solid solu- Figure 1. Features of preferential enrichment (PE) of aracemic crystal in case of substantial enrichment of the (+ +)-enantiomer in the mother liquor after the first recrystallizationo fc hiral racemic organic compounds including 1-5. tion)" of ar andom alignment of two enantiomers in the crystals.…”
Section: Introductionmentioning
confidence: 99%
“…21.5. The related, fascinating phenomenon of preferential enrichment as developed by Tamura and co-workers is also discussed in this chapter [39,40]. The phase diagram of Fig.…”
Section: Preferential Crystallisationmentioning
confidence: 94%